Outcomes of Direct Pulp Capping by Using Either ProRoot Mineral Trioxide Aggregate or Biodentine in Permanent Teeth with Carious Pulp Exposure in 6- to 18-Year-Old Patients: A Randomized Controlled Trial - Nuttaporn Parinyaprom (2018)
© 2017 American Association of Endodontists. Introduction: This study aimed to compare the success rates of direct pulp capping (DPC) by using either ProRoot Mineral Trioxide Aggregate (MTA) or Biodentine in the cariously exposed permanent teeth of 6- to 18-year-old patients. Gray discoloration was also evaluated. Methods: Fifty-nine cariously exposed permanent teeth, including teeth with diagnosis of normal pulp, reversible pulpitis, or irreversible pulpitis, early periapical involvement, and exposure size of up to 2.5 mm, were included. Each patient with only 1 cariously exposed tooth was randomly allocated to DPC with either ProRoot MTA (n = 30) or Biodentine (n = 29). Patients were recalled every 6 months. Clinical and radiographic examinations were used to determine success. Results: Fifty-five patients (mean age, 10 ± 2 years), 27 treated with ProRoot MTA and 28 with Biodentine, were included in the analysis. At mean follow-up of 18.9 ± 12.9 months, the success rate was 92.6% with ProRoot MTA and 96.4% with Biodentine (P > .05; difference, 4%; 95% confidence interval [CI], -8% to 16%). Biodentine was non-inferior to ProRoot MTA. Failures were distributed equally in all categories of pulpal diagnosis and occurred in teeth with no periapical involvement and small exposures (0.5 mm). The survival probabilities of DPC with ProRoot MTA and Biodentine were 0.92 (95% CI, 0.73-0.98) and 0.96 (95% CI, 0.80-0.99). No significant difference was observed between them (P > .05). Gray discoloration was observed only with ProRoot MTA (55%). Conclusions: Biodentine was non-inferior to ProRoot MTA when used as a DPC material for cariously exposed permanent teeth of 6- to 18-year-old patients. However, Biodentine did not cause any gray discoloration in this study.